2018
DOI: 10.1002/jssc.201700995
|View full text |Cite
|
Sign up to set email alerts
|

Selective enrichment of N‐linked glycopeptides and glycans by using a dextran‐modified hydrophilic material

Abstract: Glycosylation analysis of proteins from biological sources utilizing mass spectrometry based approaches is challenging due to the relatively low abundance of glycopeptides, the structural diversity of glycans, and the coexisting matrices. In this study, a customized dextran-bonded silica-based stationary phase was introduced for selective enrichment of glycopeptides and glycans from complex biological samples. This material has exhibited superior selectivity and broader glycosylation site coverage over commerc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 40 publications
1
5
0
Order By: Relevance
“…In a comparison of boronate affinity, Zwitterionic (ZIC)‐HILIC and PGC methods for glycopeptide enrichment, boronic acid chemistry was found to preferentially capture glycopeptides with high mannose glycans, ZIC‐HILIC enriched most N ‐glycopeptides and did not show significant preference during enrichment, and PGC was found to be not suitable for separating glycopeptides with a long amino acid sequence (Xue et al, 2018). In another study, identical results were obtained with Sepharose, PGC and dextran‐bonded silica for the separation of complex N ‐glycans (Chen, Ding, et al, 2018). Sun, Xiong, et al (2018) have developed a D‐allose@SiO 2 matrix and found that enrichment of sialylated glycopeptides was notably higher than with the commercially available Sepharose CL‐6B or TiO 2 resins.…”
Section: Studies On Specific Carbohydrate Typessupporting
confidence: 54%
“…In a comparison of boronate affinity, Zwitterionic (ZIC)‐HILIC and PGC methods for glycopeptide enrichment, boronic acid chemistry was found to preferentially capture glycopeptides with high mannose glycans, ZIC‐HILIC enriched most N ‐glycopeptides and did not show significant preference during enrichment, and PGC was found to be not suitable for separating glycopeptides with a long amino acid sequence (Xue et al, 2018). In another study, identical results were obtained with Sepharose, PGC and dextran‐bonded silica for the separation of complex N ‐glycans (Chen, Ding, et al, 2018). Sun, Xiong, et al (2018) have developed a D‐allose@SiO 2 matrix and found that enrichment of sialylated glycopeptides was notably higher than with the commercially available Sepharose CL‐6B or TiO 2 resins.…”
Section: Studies On Specific Carbohydrate Typessupporting
confidence: 54%
“…Hydrophilic interaction chromatography (HILIC) is considered as a mixed-mode mechanism, mainly based on hydrophilic partitioning and other interactions such as electrostatic interactions, dipole interactions, adsorption, hydrogen bonding, and so on . With excellent hydrophilicity and similar polyhydroxy structure, several polysaccharide-modified materials have been widely employed in HILIC mode to enrich glycopeptides, such as glucose, maltose, , cellulose, glucose-6-phosphate, chitosan, , sepharose, and dextran. , There are some advantages, such as high glycosylation coverage and unbiased recognition ability for glycopeptides, as well as excellent compatibility with MS analysis. However, there are still some difficulties to be improved.…”
mentioning
confidence: 99%
“…19 With excellent hydrophilicity and similar polyhydroxy structure, several polysaccharidemodified materials have been widely employed in HILIC mode to enrich glycopeptides, such as glucose, 20 maltose, 21,22 cellulose, 23 glucose-6-phosphate, 24 chitosan, 25,26 sepharose, 27 and dextran. 28,29 There are some advantages, such as high glycosylation coverage and unbiased recognition ability for glycopeptides, as well as excellent compatibility with MS analysis. However, there are still some difficulties to be improved.…”
mentioning
confidence: 99%
“…Until now, MS has been extensively applied in proteomics analysis with the advantages of rapid analysis speed and high sensitivity [11,12]. However, there are still many obstacles in the direct identification of target analytes by MS, owing to the complexity of biological samples, the low abundance, and ionization efficiency of glycopeptides [13,14]. Thus, efficiently enriching glycopeptides from complex biological samples before MS analysis is necessary [15].…”
Section: Introductionmentioning
confidence: 99%